Optimal Configuration of Finite Source Heat Engine Cycle for Maximum Output Work with Complex Heat Transfer Law - Li, Jun; Chen, Lingen (Journal of non-equilibrium thermodynamics, 2022)
A finite source heat engine’s optimal configuration is studied. The model includes thermal resistance, heat leakage, a complex heat transfer law, and a heat source with variable temperature. The optimization objective is that the output work is the largest. The influences of factors such as the heat transfer law and heat leakage are analyzed. The results of this paper are universal and inclusive, and provide certain theoretical support for the performance improvement of actual heat engines.